Characterization Techniques to Assess Recyclability in Dynamic Polymer Networks - Lagron, André B.; El-Zaatari, Bassil M.; Hamachi, Leslie S. (Frontiers in Materials, 2022)
The inclusion of dynamic covalent bonds in cross-linked polymer networks enables material reprocessing towards a circular economy. Bond dynamicity in this class of materials, called covalent adaptable networks (CANs), is characterized by a mixture of spectroscopic chemical and bulk materials techniques. These characterization methods illustrate the interdisciplinary nature of the field, bridging fundamental chemical insights with engineering-driven applications. Here, we seek to describe and highlight the complementary nature and nuances of these methods with an emphasis on practical applications for newcomers to the field.